2014
DOI: 10.1149/2.0151412jss
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nano-Scale Protective Oxide Films: Application on Metal Chemical Mechanical Planarization

Abstract: This study focuses on the characterization of nano-scale metal oxide films for chemical mechanical planarization (CMP) applications. The protective nature of the self-grown metal oxide layers in the CMP slurry environment enable topographic selectivity required for metallization of interconnects. Tungsten was selected as the model metal film to study the formation and characteristics of the metal oxide nano-layers since tungsten CMP is very well-established in conventional semiconductor manufacturing. The tung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…20 Furthermore, the surface oxide structures and the roughness correlate to the CMP removal rate and defectivity performance. 17 The passive film formation was confirmed by the X-Ray Reflectivity measurements and the Pilling-Bedworth ratio calculations. The AFM images taken on the passivated W surfaces align with the proposed nucleation and growth mechanisms as it is further discussed in the next section.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…20 Furthermore, the surface oxide structures and the roughness correlate to the CMP removal rate and defectivity performance. 17 The passive film formation was confirmed by the X-Ray Reflectivity measurements and the Pilling-Bedworth ratio calculations. The AFM images taken on the passivated W surfaces align with the proposed nucleation and growth mechanisms as it is further discussed in the next section.…”
Section: Resultsmentioning
confidence: 69%
“…In earlier studies, we have demonstrated the formation of tungsten oxide and titanium oxide passive films and their effects on surface energy and topography for the CMP applications. 17,18 Here, we extend these analyses to W, Ti and TiN layers to investigate their corrosion behavior and passivation characteristics as a function of H 2 O 2 (oxidizer) concentration. Electrochemical analyses indicate that the higher is the oxidizer concentration, the faster is the rate of passivation, which is further related to the increase in the material removal rates (MRR).…”
mentioning
confidence: 99%
“…It was found that stresses depend both on the metal and oxide volume, on their crystalline structures, as well as on the mechanism of oxide growth. When the oxide forms on the metal/oxide joint, the volume change due to the oxide formation can be expressed by means of Pilling-Bedworth (PBR) relationship (1) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results of studies show that the fractal analysis results are affected by operational parameters and by the type of formed oxide layers. Kargoz et al [5] concentrated on studying nanoscale metal oxide films used for chemical mechanical planarization (CMP) applications. The studies were carried out on thin metal oxide layers formed chemically from tungsten in the environment of a CMP suspension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation